HUBUNGAN ANTARA AKTIVITAS ANAK DALAM PERMAINAN BALOK DENGAN KREATIVITAS ANAK USIA DINI - Rima Nabila Maulani; Teti Ratnassih; Nano Nurdiansah (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2024)
This study aims to find out: (1) Children's activities using block games in Group A of RA Nurul Huda II Tasikmalaya; (2) Children's creativity in group A RA Nurul Huda II Tasikmalaya; (3) The relationship between children's activities in block games to children's creativity in group A RA Nurul Huda II Tasikmalaya. The approach in this study uses a quantitative method of correlation. The data collection instrument uses a scale with four answer choices. The subject of this study is Early Childhood children in group A RA Nurul Huda II Tasikmalaya as many as 20 people. The data collection techniques used are observation, interviews and documentation. The analysis tools used are simple linear regression analysis, correlation test, determination coefficient analysis and non-determination test as well as hypothesis test. From the results of the study, it is known that for the regression test, the equation Å¶ = 3.87 + 0.95 X This means that Children's Activities in Block Games carried out by RA Nurul Huda II Tasikmalaya students have a positive effect on Early Childhood Creativity by 0.95 times. The correlation coefficient (r) of 0.80 which can be interpreted as the influence of Children's Activities in Block Play on Early Childhood Creativity is very strong. The determination test obtained a value of 64% which illustrates the large percentage of the influence of Children's Activities in Block Play on Early Childhood Creativity. The non-determination test, which is 36%, is the percentage of influence of other factors on Early Childhood Creativity of RA Nurul Huda II Tasikmalaya. The hypothesis test is known to have a ttable value of Î± = 0.25 and dk = 18, which is 0.688 while the tcount value is 5.65. This shows that the tcal>ttable (5.65 > 0.688). So that Ho is rejected or Ha is accepted, it means that Children's Activities in Block Games have a significant effect on Early Childhood Creativity of RA Nurul Huda II Tasikmalaya Cisayong